Anak Berkebutuhan Khusus dalam Perspektif Psikologi Pendidikan Islam: Kajian Konsep, Prinsip, dan Strategi Pembelajaran - Riski Kristianto Pambudi; Siti Rohimah (Lembaga Yasin AlSys, 2026)
Education for children with special needs requires a pedagogical framework that is oriented not only toward meeting learning needs but also toward recognizing the dignity, potential, and uniqueness of each child. This study aims to examine the concept of children with special needs from the perspective of Islamic educational psychology comprehensively, including basic principles, learning strategies, and the roles of various parties in realizing dignified education for children with special needs. This study used a literature study or library research method with a descriptive-analytical approach to relevant literature in the fields of Islamic educational psychology, inclusive education, and education for children with special needs. The results of the study show that Islamic educational psychology offers a holistic framework that integrates physical, ‘aqliyah, nafsiyah, and ruhaniah dimensions in understanding children with special needs. Islam views children with special needs as noble creatures created by Allah Swt. who possess fitrah and potential that need to be optimally developed. Principles of Islamic educational psychology such as rahmah, patience, tawakkal, justice, and recognition of individual uniqueness serve as spiritual and moral foundations in the education of children with special needs. Islamic value-based learning strategies for children with special needs include adaptive differentiated learning, the use of Islamic multisensory media, and Islamic guidance and counseling. The success of education for children with special needs is strongly determined by synergy among families, Islamic educational institutions, and Muslim communities. The conclusion of this study affirms that the integration of Islamic values in the education of children with special needs provides a conceptual contribution to the development of Islamic educational psychology while offering practical guidance in building inclusive education that is dignified, adaptive, and aligned with Islamic teachings.